Development of Mawashi Geri Cudan Training Variations for Male Karate Athletes: A Comprehensive Approach to Enhancing Technical Proficiency and Training Engagement - Kevin Salomo Hutagalung; Samsuddin Siregar (Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2025)
Objectives: Traditional karate training methodologies often employ repetitive, monotonous approaches that may limit athlete development and reduce training motivation. Mawashi Geri Cudan, a fundamental circular kick technique targeting the middle body section, requires systematic training variations to optimize skill acquisition and maintain athlete engagement throughout extended training periods. This research aimed to develop, validate, and evaluate comprehensive training variations for Mawashi Geri Cudan technique among male karate athletes, addressing current limitations in traditional training methodologies while maintaining technical integrity and safety standards. Methods: This study employed a comprehensive Research and Development (R&D) methodology following Sugiyono's developmental model, conducted across November 2024. Participants included 30 male karate athletes (ages 12-18 years) with white, yellow, and orange belt classifications from three established dojos in Medan, Indonesia. The development process incorporated systematic needs analysis, expert validation by sports science specialists, certified karate coaches, and language experts, followed by sequential field testing phases. Nine distinct training variations were developed based on motor learning principles and progressive skill development frameworks. Data collection utilized structured questionnaires employing 5-point Likert scales, with analysis conducted through descriptive quantitative methods and percentage-based feasibility assessments. Results: The development process successfully created nine evidence-based training variations addressing different aspects of Mawashi Geri Cudan skill development. Expert validation demonstrated progressive improvement across validation stages: sports science experts rated variations 78% (feasible) initially, improving to 82% (highly feasible) post-revision; coaching experts provided ratings advancing from 80% (feasible) to 100% (highly feasible); language experts showed improvement from 60% (moderately feasible) to 84% (highly feasible). Small group trials (n=10) achieved 80% feasibility rating, while large group trials (n=20) demonstrated 88% (highly feasible) rating. Statistical analysis revealed significant improvement in participant engagement and perceived training effectiveness compared to traditional methodologies. Conclusion: The developed Mawashi Geri Cudan training variations demonstrated high feasibility, technical accuracy, and practical applicability for implementation in karate training programs. The systematic development approach successfully addressed monotony concerns while maintaining adherence to proper karate principles, providing coaches with evidence-based tools for enhanced instruction and athlete development.